2009
DOI: 10.1055/s-0029-1240611
|View full text |Cite
|
Sign up to set email alerts
|

Minor Secondary Metabolic Products from the Stem Bark ofPlumeria rubraLinn. Displaying Antimicrobial Activities

Abstract: Four new iridoids viz., plumeridoids A, B, and C and epiplumeridoid C were isolated from the stem bark of Plumeria rubra Linn. together with twenty-four known compounds viz., 1-( P-hydroxyphenyl)propan-1-one, isoplumericin, plumericin, dihydroplumericin, allamcin, fulvoplumerin, allamandin, plumieride, P- E-coumaric acid, 2,6-dimethoxy- P-benzoquinone, scopoletin, cycloart-25-en-3 beta,24-diol, 2,4,6-trimethoxyaniline, ajunolic acid, ursolic acid, oleanolic acid, beta-amyrin acetate, betulinic acid, lupeol and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…The plant has been investigated for antibacterial (Hamburger et al, 1991;Egwaikhide et al, 2007Egwaikhide et al, , 2009Kuigoua et al, 2010;Baghel et al, 2010;Dey et al, 2011), antifungal (Kuigoua et al, 2010;Souza et al, 2011;Gaitan et al, 2011), antimicrobial (Mahady, 2002), antialgal (Kuigoua et al, 2010), larvicidal (Ramos et al, 2009;Patil et al, 2012), molluscicidal (Hamburger et al, 1991), piscicidal (Joshi and Joshi, 2006), nematicidal (Joymati, 2010), antioxidative and free radical scavenging activities (Ruiz-Teran et al, 2008), hypolipidemic (Merina et al, 2010), proteolytic (De Freitas et al, 2010), cytotoxic (Kardono et al, 1990;Hamburger et al, 1991;Rekha and Jayakar, 2011), abortifacient (Dabhadkar and Zade, 2012) and anti HIV (Tan et al, 1991) properties. The biocatalytic activity in terms of lipase activity in hydrolysis and acyl transfer reactions of latex was compared with that of babaco (Vasconcellea x Heilbornii Cv.)…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…The plant has been investigated for antibacterial (Hamburger et al, 1991;Egwaikhide et al, 2007Egwaikhide et al, , 2009Kuigoua et al, 2010;Baghel et al, 2010;Dey et al, 2011), antifungal (Kuigoua et al, 2010;Souza et al, 2011;Gaitan et al, 2011), antimicrobial (Mahady, 2002), antialgal (Kuigoua et al, 2010), larvicidal (Ramos et al, 2009;Patil et al, 2012), molluscicidal (Hamburger et al, 1991), piscicidal (Joshi and Joshi, 2006), nematicidal (Joymati, 2010), antioxidative and free radical scavenging activities (Ruiz-Teran et al, 2008), hypolipidemic (Merina et al, 2010), proteolytic (De Freitas et al, 2010), cytotoxic (Kardono et al, 1990;Hamburger et al, 1991;Rekha and Jayakar, 2011), abortifacient (Dabhadkar and Zade, 2012) and anti HIV (Tan et al, 1991) properties. The biocatalytic activity in terms of lipase activity in hydrolysis and acyl transfer reactions of latex was compared with that of babaco (Vasconcellea x Heilbornii Cv.)…”
Section: Pharmacologymentioning
confidence: 99%
“…Chavero and Roces (1988) Phytochemistry: Iridoids such as fulvoplumierin, allamcin, allamandin, plumericin, 15-demethylplumieride, plumieride, alpha-allamcidin, beta-allamcidin and 13-O-trans-pcoumaroylplumieride; 2,5-dimethoxy-p-benzoquinone and lignan liriodendrin were isolated from the bark of Indonesian P. rubra (Kardono et al, 1990). Furthermore, four new iridoids such as plumeridoids A, B and C and epiplumeridoid C and several known compounds like 1-(P-hydroxyphenyl) propan-1-one, isoplumericin, plumericin, dihydroplumericin, allamcin, fulvoplumerin, allamandin, plumieride, P-E-coumaric acid, 2,6-dimethoxy-P-benzoquinone, scopoletin, cycloart-25-en-3 beta,24-diol, 2,4,6-trimethoxyaniline, ajunolic acid, ursolic acid, oleanolic acid, beta-amyrin acetate, betulinic acid, lupeol and its acetate, 2,3-dihydroxypropyl octacosanoate, glucoside of beta-sitosterol, stigmasterol and beta-sitosterol were reported from the plant species (Kuigoua et al, 2010). Cardiac glycosides were also found to be present (Radford et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…14 Generally, possess significant anti-inflammatory, analgesic, antibacterial, antifungal, antitumor activities, antioxidant, antiviral, anxiolytic and purgative activities. 13,[15][16][17][18][19] The iridoid plumieride has been isolate from several genus like Allamanda, Himatanthus, Plantago and Plumeria in different yields. [20][21][22][23][24][25] Plumieride shows antidermatophytic, antifungal, plant growth inhibitory potential and in vitro cytotoxicity against radiationinduced fibrosarcoma (RIF) tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…10 It has been reported that distinct parts of Fringpiani have diverse biological properties. Pod has abortifacient, 11 hepatoprotective 12 effects; bark is antinociceptive and anti-inflammatory. 13 Leaves are found to have antiulcer activity, 14 whereas flowers have profound antioxidant effects.…”
Section: Introductionmentioning
confidence: 99%